Washington View: Will the light shine on education?. (April 2016) - Ferguson, Maria
In the current election season, education is not drawing a lot of interest as a political issue. According to Gallup, only 4% of Americans consider education the nation's most important problem. Hillary Clinton created a dustup last year when she talked about charter schools and may end up avoiding all but the simplest comments about it. But Sen. Bernie Sanders has put forth a proposal to make public colleges and universities free. The Republicans mostly avoid the topic except to take broadsides at the Common Core and keeping the federal government out of education. But it will be interesting to see if after the two major parties select their nominees that education becomes a more important issue in the fall campaign.